Problems in Organising Non-Formal Religious Education - Muhammad Zailani; Abdul Fattah Nasution; Nasrun Salim Siregar (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2024)
Although the purpose of majelis taklim is to provide knowledge to the community, the results have not been as expected. The community has not changed in their understanding of science, and some have even become less interested in going to majelis taklim. The purpose of this research is to study the problems faced by Majelis Taklim Al-Mursyid in Bandar Khalipah Village, Percut Sei Tuan Sub-district, Deli Serdang Regency, as well as the activities carried out there. Another objective is to find solutions to the problems faced by the Majelis Taklim. This type of research is qualitative research that uses a descriptive approach and uses observation, interviews, and documentation as data collection techniques. In addition, they used data analysis for collection, reduction, presentation, and conclusion. The results of this study show several problems that arise in the implementation of recitation in majelis taklim. Among these problems are that the administrators do not have enough responsibility to complete their tasks because there is no more food or alms after the recitation, the mad'u do not like the direct practice done by the ustadz, not enough media, and lack of understanding of the lecture. In addition, to overcome the problems of majelis taklim, the administrators should be given greater attention to the issue of organisational structure. This should help them understand religious knowledge, make suggestions to equip the necessary media, adapt the material to the needs of the mad'u, and understand the purpose of majelis taklim.